ANALISIS KEMAMPUAN PARAFRASE MAHASISWA BARU UIN SUMATERA UTARA SEBAGAI UPAYA PENCEGAHAN PLAGIARISME - Parulian Sibuea; Ibtihaz Salma; Khaila Zahrani Lubis; Adiva Zuhaira; Alana Alfarisha Br Bako (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study focuses on evaluating the paraphrasing skills of first-year students at the State Islamic University of North Sumatra to help reduce cases of plagiarism in their academic work. Paraphrasing is an important skill in academia that allows students to express ideas found in reference materials in their own words while maintaining the original meaning. A descriptive qualitative method was used in this study, with data collection through literature analysis, semi-structured interviews, and paraphrasing assessment using a special research tool. The research participants were first-year students from the State Islamic University of North Sumatra who were assigned to paraphrase the same text. The results of the study showed that, in general, students had a fairly good level of paraphrasing ability. However, they faced difficulties such as limited use of synonyms, sentence constructions that were too similar to the original text, and weak understanding of key concepts. In addition, factors such as low academic literacy and time constraints hindered the quality of their paraphrasing efforts. Therefore, continuous and structured training in paraphrasing is essential to improve the originality of students' academic writing and help avoid plagiarism.